PENGARUH LINGKUNGAN KERJA, KOMITMEN PROFESI, MOTIVASI DAN STRES KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA PEKANBARU TAMPAN - Santi Liasari Harahap (Manajemen dan Bisnis, 2020)
The problems in this research are: how the influence of the work environment, professional commitment, motivation and work stress partially and jointly on the performance of employees at the Pratama Pekanbaru Tax Service Office Handsome ?. Research objectives: To find out the effect of the work environment, professional commitment, work motivation and stress partially and jointly on employee performance at the Pratama Pekanbaru Tax Office Handsome. The hypothesis proposed is: Work environment, professional commitment, work motivation and stress partially and simultaneously have a significant effect on employee performance at the Pratama Pekanbaru Tampan Tax Office. The study was conducted at the Pratama Pekanbaru Tax Service Office Handsome Road Ring Road Arengka II / SM Amin Road Simpang Baru Pekanbaru, with a population of 98 people, and a study sample of 96 people. Based on the results of the analysis, there is a significant influence between the work environment on the performance of the Pratama Pekanbaru Tampan Tax Office employees, because according to the results of the analysis t count t-table (2.932 1.67) at n = 96 with a 95% significance level. There is a significant influence between the professional commitment to the performance of the Pratama Pekanbaru Tampan Tax Office employees, the result of the analysis is t count t-table (1.975 1.67) at n = 96 with a significance level of 95%. There is a significant influence between work motivation on the performance of the Pratama Pekanbaru Tampan Tax Office employee, because according to the results of the analysis t count t-table (2.007 1.67) at n = 96 with a significance level of 95%. There is a significant effect between work stress on the performance of the Pratama Pekanbaru Tampan Tax Office employees, because according to the results of the t-count analysis t-table (-1.605 1.67) at n = 96 with a significance level of 95%. Value of F-count F table (14,321 2,46) together (multiple) there is a positive and significant influence of work environment, professional commitment, motivation and work stress on the performance of the Pratama Pekanbaru Tampan Tax Office employees. Thus the hypothesis proposed is accepted by the truth.